IMPLEMENTASI STRATEGIC CORPORATE SOCIAL RESPONSIBILITY DALAM PERSPEKTIF SHARI’AH ENTERPRISE THEORY - Ririn Irmadariyani (UPT Penerbitan Universitas Jember)
This article aimed to review the implementation of strategic corporate social responsibility in the perspective shari’ah enterprise theory. Three theories (entity theory, enterprise theory, and shari’ah enterprise theory) used to assess the implementation of strategic corporate social responsibility in the roles and responsibilities of management paradigm in run companies in order to provive welfare to stakeholders. The results indicate that third theory give the meaning of welfare differently. Based on ethics, entity theory is egoism, enterprise theory is utilitarianism, shari’ah enterprise theory is teonom, so that the level involvement strategic corporate social responsibility is also different. Egoism and utilitarianism different because it has different perspective, but both have a moral issue study that the same that is based on human reason without the link the power of the God. It can be said that activities performed to makes welfare to stakeholders is secular. Shari’ah enterprise theory is teonom which means consider of spiritual awareness in man, so that the activity of strategic corporate social responsibility done by companies based worship to the God. Shari’ah enterprise theory makes welfare to stakeholders of shari’ah value added.